1992
DOI: 10.1016/s0196-0644(05)82650-2
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous adenosine in the prehospital treatment of paroxysmal supraventricular tachycardia

Abstract: Adenosine appears to be effective and safe for the pre-hospital treatment of PSVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…Adenosine is an effective treatment for supraventricular tachycardias (SVTs) excluding atrial fibrillation/flutter and atrial tachycardia, with high rates of conversion to sinus rhythm 1 2. Small prospective studies have demonstrated that administration of adenosine in a community setting is safe2 3 and there is a good correlation between paramedics' interpretation of the ECG and that of physicians 4 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine is an effective treatment for supraventricular tachycardias (SVTs) excluding atrial fibrillation/flutter and atrial tachycardia, with high rates of conversion to sinus rhythm 1 2. Small prospective studies have demonstrated that administration of adenosine in a community setting is safe2 3 and there is a good correlation between paramedics' interpretation of the ECG and that of physicians 4 5.…”
Section: Introductionmentioning
confidence: 99%
“…Small prospective studies have demonstrated that administration of adenosine in a community setting is safe2 3 and there is a good correlation between paramedics' interpretation of the ECG and that of physicians 4 5. In cases where there has been inappropriate administration of adenosine, this had not been associated with adverse outcomes2 6 and, with training, inappropriate administration rates are reduced 7. To date, all studies examining the use of adenosine in the prehospital setting required all patients to be taken to hospital even if the arrhythmia had successfully been terminated.…”
Section: Introductionmentioning
confidence: 99%
“…A second tecadenoson bolus recruited more conversions in all regimens except in E, perhaps representing a saturation of the AV nodal receptors (14) 2 (14) 4 (14) 5 (22) 5 (22) 18 (18) Ventricular ectopy 1 (17) 2 (14) 1 (7) 3 (11) 5 (22) 5 (22) 16 (16) Second-degree AV block 0 0 0 2 (7) 4 (17) 6 (26) 12 ( after the first tecadenoson dose in regimen E. The rate of conversion of PSVT in tecadenoson regimen C is close to what has been reported with adenosine (85% to 96%). [11][12][13] The median time to tecadenoson-related conversion was also dose dependent. Conversion occurred in Ͻ1 minute with the 3 highest dose regimens (300/600, 450/900, and 900 g/900 g) but was Ͼ2 minutes for the 2 lower dose regimens (75/150 and 150 g/300 g.…”
Section: Discussionmentioning
confidence: 94%
“…These treatments include vagal manoeuvres, intravenous adenosine, and electrical cardioversion. 4 Previous studies have established the value and safety of treating these patients out of the hospital, [5][6][7][8][9] but the evidence base for an SVT T + R protocol is sparse.…”
Section: Introductionmentioning
confidence: 99%